Penggunaan Media Gambar Dalam Meningkatkan Minat Belajar Siswa dengan tema hobiku yang menarik Kelas V SD Negeri 76 Tarowang - Indri Yani; Nur Hilal Aulia Rizky R; Besse Syukroni Baso; Haris (STKIP Subang, 2025)
This study aims to improve students’ learning interest through the use of picture media with the theme My Interesting Hobby in grade V at SD Negeri 76 Tarowang. The research subjects consisted of 28 students. The method applied was Classroom Action Research (CAR), conducted in two cycles, each consisting of four meetings with the stages of planning, implementation, observation, and reflection. In the first cycle, learning was carried out individually with assessments in the form of written tests, while in the second cycle the focus shifted to group work through discussions, written products, and simple presentations. Data were collected using observation sheets of student activities and assessment results. The findings showed an increase in student activeness from an average of 55.35% in the first cycle to 83% in the second cycle. The average assessment score also improved from 68 (fair category) in the first cycle to 87 (good category) in the second cycle. These results confirm that the use of picture media not only enhances students’ learning interest but also fosters greater confidence, active participation, and the ability to produce higher-quality work.